The other car workers: work, organisation and technology in the maritime car carrier industry (Basingstoke, 2006)
"About 60 million vehicles are produced each year, of which eight million are shipped by deep-sea and millions more by short-sea routes. This makes the maritime car carrier sector an integral part of car manufacturing's supply chain. Yet the sector has been entirely neglected by social scientists. Switching attention from the frequently researched car assembly-line worker, this book documents the dramatic new developments that have taken place in the industry both in production systems, technology, organisational infrastructure and not least, in terms of working life. It examines the maritime car carrier sector with respect to changes in cost structure and dynamics; in ownership, freight, labour and other markets; in technological innovation and ship design; and in relation to car manufacturers, ship management companies and crewing agents. Alongside a political economy of the industry, chapter and verse is provided on the work and lives of the seafarers who make up its global labour force, many of them from low-wage countries. It is seen that in terms of their work-life balance and in other respects they endure conditions that have no land-based equivalents."